Best L2 Local Approximation on Two Small Intervals. (1st February 2016) - Cuenya, H. H.; Ferreyra, D. E.; Ridolfi, C. V.
ABSTRACT: In this article, we introduce the τ condition, which is weaker than the L 2 differentiability. If a function satisfies the τ condition on two points of ℝ, we prove the existence and characterization of the best local polynomial approximation on these points.